Classic Rock Tours 4. Long Walks, Lost Documents and the Birthplace of Igneous Petrology: Exploring Glen Tilt, Perthshire, Scotland - Kerr, Andrew (Geoscience Canada, 2020)
The spectacular angular unconformity at Siccar Point is the most famous site associated with James Hutton (1726–1797), but it was not his only place of insight. In 1785, three years before he discovered Siccar Point, Hutton examined outcrops in the still-remote valley of Glen Tilt, in the Scottish Highlands. He documented contact relationships between Precambrian metasedimentary rocks and Paleozoic granite bodies, although he had no knowledge of their true ages. Near to the hunting lodge where he and his colleague John Clerk of Eldin stayed, veins of granite clearly cut through relict bedding in the stratified rocks and disrupt their layering, breaking apart individual strata and leaving fragments (xenoliths) surrounded by granite. Hutton correctly deduced that the granite must originally have been in a ‘state of fusion’ and was forcefully injected into much older ‘schistus’. Such conclusions contravened prevailing ideas that granite bodies formed from aqueous solutions, and also refuted a wider philosophical view that granite and other crystalline rocks were the oldest and first-created parts of the Earth. Hutton’s key outcrops in Glen Tilt are easy to visit, although they do require a long (but easy) roundtrip hike of some 25 km. These are certainly not the most spectacular intrusion breccias that I have ever seen, but they are very instructive, and were very influential, because they sparked a long, and at times acrimonious, debate about the origins of igneous rocks and especially granite. This controversy had many strange twists and turns. These include the disappearance of Hutton’s original manuscript after his death, and its serendipitous rediscovery a century later, and the similar loss and rediscovery of exquisite drawings by John Clerk, almost two centuries after they were first penned. Among the lost drawings is an early example of detailed outcrop-scale mapping, which would become a key field-work technique. Hutton’s vision of granite as the product of hot, liquid material that moved upward in the Earth’s crust (plutonism) eventually prevailed over the idea that crystalline rocks formed from a primordial ocean that once enveloped the Earth (neptunism), but this victory did not come easily or quickly. In another strange twist of history, new evidence from the Cape of Good Hope in South Africa eventually acted to further the plutonist cause. Glen Tilt has changed very little since the time of Hutton, but the observations that were made here, and the long debate that followed, brought fundamental changes in our understanding of the Earth. Although Siccar Point should remain the first entry on the bucket list of any prospective geopilgrim to Scotland, the long and beautiful valley of the River Tilt should also be a priority.